Electra’s Oracle: A Schizo-Geo-Analytical Account of Accelerationist Hyperstition: Електрината пророчица: Шизо-гео-аналитички оглед за акселерационистичката хиперстиција - von Samsonow, Elisabeth; Šišovski, Jordan (Identities: Journal for Politics, Gender and Culture, 2016)
Author(s): Elisabeth von Samsonow | Елизабет вон Самсонов Title (English): Electra’s Oracle: A Schizo-Geo-Analytical Account of Accelerationist Hyperstition Title (Macedonian): Електрината пророчица: Шизо-гео-аналитички оглед за акселерационистичката хиперстиција Translated by (English to Macedonian): Jordan Šišovski | Јордан Шишовски Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 12, No. 1-2 (Winter 2015 - Summer 2016) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 60-80 Page Count: 20 Citation (English): Elisabeth von Samsonow, “Electra’s Oracle: A Schizo-Geo-Analytical Account of Accelerationist Hyperstition,” Identities: Journal for Politics, Gender and Culture, Vol. 12, No. 1-2 (Winter 2015 - Summer 2016): 60-80. Citation (Macedonian): Елизабет вон Самсонов, „Електрината пророчица: Шизо-гео-аналитички оглед за акселерационистичката хиперстиција“, превод од англиски Јордан Шишовски, Идентитети: списание за политика, род и култура, т. 12, бр. 1-2 (зима 2015 - лето 2016): 60-80.